Bioaccumulation and translocation of heavy metals by Ceratophyllum demersum from Skadar Lake, Montenegro - Kastratović Vlatko; Krivokapić Slađana; Bigović Miljan; Đurović Dijana; Blagojević Nada (Journal of the Serbian Chemical Society, 2014)
Lacustrine systems are very complex water systems in terms of transport and interaction of heavy metals. Primarily, due to its high variability and current chemical parameters, macrophytes’ tissue is a more plausible bio-indicator of the level load of metals within lake ecosystems than water or sediment analyses are. The macrophyte, Ceratophyllum demersum, sampled from Skadar Lake in Montenegro has been used as a bio-indicator. Sediments, water and plants were examined on the contents of ten metals in four different periods in 2011. The concentrations of the metals followed the trend: sediment > leaf C. demersum > stem C. demersum > water. There are differences in the sequences of the metal content in the plant compared to the sequences of their bioaccumulation (BCF) ability. This difference suggests a different capacity of macrophytes for certain metals. BCF for Mn is several times higher compared to other metals. The highest ratio of leaf/stem concentrations was recorded for Mn (2.19) and the lowest was for Pb (1.04). The highest contents of Cd, Co, Cr, Pb, V, and Sr were found in the tissues of C. demersum at the beginning of the growing season; whereas Ni, Zn, Cu and Mn were found at the end of the vegetative phase.